(untitled) (Sains Humanika, 2024)
In order to ensure that the Malaysian automotive industry is able to compete with the world market, continuous workplace learning must be in place. This is to ensure existing employees in the automotive industry maintain productivity and competitiveness. This study is conducted to identify the element of TPACK to further explore the component of in-house training framework for the automotive industry. This study uses a sequential exploratory mixed method model as a research design. The components of TPACK for the in-house training framework have been identified through the use of expert interviews. The interview phase featured seven panels, including technical trainers and academics with expertise in automotive industry. Data on the suitability of the TPACK elements was gathered quantitatively using questionnaires. The survey included 114 automotive technical trainers in total as a sample. Pedagogical knowledge (PK) comprises 22 out of the 36 training elements that were found to be the majority. The findings of this study also suggest the importance for technical trainers to integrate the TPACK model in the development of in-house training in the automotive industry. By integrating the TPACK model, a comprehensive in-house training can be developed and implemented.